Apprentissage du français en Suisse alémanique : des systèmes éducatifs aux situations extra-scolaires - Pekarek Doehler, Simona; Saudan, Victor; Lüdi, Georges (My University, 1996)
This contribution reports some results from a study on the acquisition of French as a second language by German speaking pupils in Switzerland. The study focuses on the link between in - and out - of-school interaction activities at various levels of the Swiss educational system in relation to the developement of practical L2 skills (discourse competence). In what follows, two interaction situations will be analyzed: conversation lessons at High School and communicative interactions of German speaking apprentices during their stay in a French speaking environment. As to the first situation, it will be shown that conversation lessons frequently offer poor contexts for the development of L2 skills, limiting often communicative language use to a minimum, and how their potential might be more fully explored. As to the second communication situation, it will be argued that the exchange of apprentices constitutes an interesting complementary context for language acquisition, besides the classroom, on condition that it is framed by what we might call the pedagogy of exchange.
Keywords: Enseignement des langues; Acquisition d'une langue seconde; Français Langue seconde; Milieu scolaire; Pédagogie; Enfant; Apprentissage; Allemand Langue maternelle; Suisse alémanique; Système éducatif